Przesłania motywów elewacji w poezji Bertranda Degotta - Lubas-Bartoszyńska, Regina (Przestrzenie Teorii, 2007)
Motives of ascending are placed in the text of the author in the domain of verticality. There are problems of dynamism of poetic space. The crossing of a horizon is characteristic for such a space. The perpetual crossing of any horizons is characteristic of Degott poetry. Both horizons apply to poetics as called in poetry ones. Their abundance and way of ascending brings plurality of symbolication. The motives of ascencion gain this poetry a trait of civilization. This is the subject in the automobile which is ascended itself.